On Noveley Inequalities for Convex Stochastic Processes on Time Scale Utilizing Quantum Operators (Analysis in Theory and Applications, 2025)
We aim to present a innovation extension of the mean-square stochastic integral of a process on time scale based on a q-operator and fractional q-operator. By presenting the q-convex definition for a stochastic process and using quantum operators, we were able to prove some well-known inequalities such as the HermitHadamardand the Jensen for the processes.